Sauyunan: Solidaritas Masyarakat dalam Proses Pelaksanaan Tradisi Rempug Tarung Adu Tomat di Kampung Cikareumbi Kabupaten Bandung Barat - Mirna Nur Alia Abdullah; Lena Nurlaena (Universitas Hamzanwadi, 2022)
This study was conducted because the researchers were interested in the existence of solidarity among the people of Kampung Cikareumbi, who were still strong in the Rempug Tarung Adu Tomat ritual. The purpose of this research is to explain the solidarity of the people of Kampung Cikareumbi in implementing the Rempug Tarung Adu Tomat tradition, which has been held every year since 2011. This research uses a descriptive method with an ethnographic approach. The study results show that the Rempug Tarung Adu Tomat tradition is a new culture as entertainment at the peak of the Ruwatan Bumi Hajat Buruan ceremony, which has been held for decades. Rempug Tarung Adu Tomat is a distinctive and unique tradition that made Cikareumbi Village famous, Cikidang Village, Lembang District.